PENGEMBANGAN BAHAN AJAR BERBASIS PRODUCTIVE STRUGGLE PADA MATERI PECAHAN KELAS V SEKOLAH DASAR - Putri Widiyawati; Muhammad Rijal Wahid Muharram; Ika Fitri Apriani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Mathematics learning on fractions in elementary schools still faces various challenges, particularly due to the use of instructional materials that tend to be monotonous, lack contextual relevance, and provide limited opportunities for students to develop a deep conceptual understanding. This condition contributes to students' low mathematical achievement, as reflected in the results of the Trends in International Mathematics and Science Study (TIMSS) 2015, in which Indonesia obtained a mathematics score of 397, remaining below the international average of 500. Therefore, this study aimed to develop productive struggle-based mathematics instructional materials for fifth-grade elementary school students on the topic of fractions. This study employed the Educational Design Research (EDR) model proposed by McKenney and Reeves (2012) and was conducted up to the second phase, namely analysis and exploration, and design and construction. The analysis and exploration phase involved teacher interviews, classroom observations, and document analysis in two elementary schools. The design and construction phase resulted in a prototype of instructional materials integrating the Realistic Mathematics Education (RME) approach with productive struggle strategies, such as guided challenges, error reflection, and the use of real-life contexts. The prototype was subsequently validated by subject matter, pedagogical, and design experts. The validation results indicated that the instructional materials achieved a feasibility score of 83.64%, categorized as highly feasible, after revisions to diction, illustrations, and visual appearance. Thus, the developed instructional materials were deemed suitable for use and are recommended for field testing to examine their practicality and impact on students' conceptual understanding. ABSTRAK Pembelajaran matematika pada materi pecahan di sekolah dasar masih menghadapi berbagai kendala, terutama karena penggunaan bahan ajar yang cenderung monoton, kurang kontekstual, dan belum memberikan ruang bagi siswa untuk mengembangkan pemahaman konsep secara mendalam. Kondisi tersebut berdampak pada rendahnya kemampuan matematika siswa, yang tercermin dari hasil Trends in International Mathematics and Science Study (TIMSS) 2015 dengan skor matematika Indonesia sebesar 397, masih berada di bawah rata-rata internasional yaitu 500. Oleh karena itu, penelitian ini bertujuan untuk mengembangkan bahan ajar matematika berbasis productive struggle pada materi pecahan kelas V sekolah dasar. Penelitian ini menggunakan model pengembangan Educational Design Research (EDR) McKenney dan Reeves (2012) yang dilaksanakan hingga tahap kedua, yaitu analisis dan eksplorasi serta desain dan konstruksi. Tahap analisis dan eksplorasi dilakukan melalui wawancara guru, observasi pembelajaran, dan studi dokumen di dua sekolah dasar. Tahap desain dan konstruksi menghasilkan prototipe bahan ajar yang mengintegrasikan pendekatan Realistic Mathematics Education (RME) dengan strategi productive struggle, seperti tantangan terarah, refleksi kesalahan, dan penggunaan konteks nyata, yang selanjutnya divalidasi oleh ahli materi, ahli pedagogik, dan ahli desain. Hasil validasi menunjukkan bahwa bahan ajar memperoleh tingkat kelayakan sebesar 83,64% dengan kategori sangat layak setelah dilakukan revisi pada aspek diksi, ilustrasi, dan tampilan visual. Dengan demikian, bahan ajar yang dikembangkan dinilai layak digunakan dan direkomendasikan untuk diuji pada tahap uji coba lapangan guna mengetahui kepraktisan serta dampaknya terhadap pemahaman konsep siswa.